Queering - Sadia Riaz (Linguistics and Literature Review, 2015)
This research paper aims at exploring the disposition of queering as an act of empowerment that accommodates all deviations, such as lesbian, gay, bisexual or transsexual, as well as the threats posed by it to conventional social/familial structure and morality. The paper extensively analyses queer theory and unravels the terrain through which it denies the normalcy of heterosexuality by blurring the gay/straight binary opposition and celebrating the plurality of responses which are made available. Consequently, it moves a step ahead in exposing structural exclusions in the Western system of knowledge and resists this stigmatization. Furthermore, this paper addresses the proposition that gender is not a natural construct; hence it should be viewed as fluid and variable. Gender is not a definition of who one is and is instead, seen in relation to ones behavior in different situations at different times, thereby becoming performative. This is a qualitative study based upon hermeneutic theory of textual analysis. For a better comprehension of the taken stance, the key concepts of queer theory are applied on Laura Loomis’ ‘Mirror Poem’ and Katy Perry’s lyrics ‘I Kissed a Girl’. Queering as a practice and notion opens up numerous possibilities for human beings to perform subjectively and boundlessly, with regard to various sexual inclinations. On the contrary, queering is also subject to religious, legal and cultural variation and in many cultures is considered as a threat to moral order.